Kapasitas aparat Inspektorat dalam pengawasan keuangan daerah kabupaten Sidoarjo (Kajian terhadap kompetensi aparat Inspektorat di kabupaten Sidoarjo) - Tuding, Daniel Saleppang (Jurnal Ilmiah Administrasi Publik, 2016)
Based on experience during five years (2007-2011), the Inspectorate as the internal supervisor of government officials at Sidoarjo, has lack capacity in playing their roles as consulting agent, enhancing quality assurance and providing early warning to prevent or reduce the potential of the irregularities in the financial management area. The results of investigation from the Institution of Finance Audit (IFA) to the Local Government Finance Report (LGFR) of Sidoarjo Regency during five years (2007-2011), indicate lack of accountability in asset and local financial management: Unnatural (2007), Fair With Exception (2008), Not Stated Opinion (2009) and Fair With Exception (2010 and 2011). These findings highlight lack of accountability and management in the form of non-compliance with laws and regulations, the fraudulance and the non-compliance with the financial statement presentation. Improving accountability and management are fundamental for better performance of the institution in the future.